Menghadirkan Anak-Anak Dalam Historiografi Indonesia - Angga Pusaka Hidayat (Pusat Studi Gender dan Anak (PSGA) Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Sultan Maulana Hasanuddin Banten, 2022)
This paper is a historiographical review of the historiography trends. There are not many historical works of Indonesia that have adopted children and childhood as the main theme. Children are often placed as periphery. Even if they are talked about, children is a complement to the gait of adults. In many ways, history is like the story of adults, even though children are also part of social life. For this reason, this paper aims to review theoretical and practical opportunities to present children in Indonesian historiography. The presence of children and their childhood proportionally in historiography is expected to show the complexity of society. The research method used for the preparation of this paper is a historiographical review, namely qualitative research on the history of historical writing. This paper proposes the view that placing children and their social roles as historical entities as important as the presence of adults and bringing the story of children and childhood at the center of historical events are several theoretical steps that make the presence of children in historiography a might happen. On the other hand, children can be the subject of discussion in historical themes such as education, the environment, and health, both at the colonial and post-colonial society.